Essays in corporate bankruptcy - Ferreira, Rafael de Vasconcelos Xavier (2014)
This thesis contains three chapters, each bringing an essay on credit markets and on the institutions governing corporate bankruptcy. In chapter one, we bring some evidence to dispute the notion that increasing creditor protection always promotes credit market development. Ever since the seminal works of La Porta et al (1997,1998), the metric of creditor protection they proposed - the creditor rights index - has been widely used in the Law and Finance literature as explanatory variable in reduced form regression models to assess how creditor protection correlates to credit market development. We explore some problems with this approach. From a theoretical standpoint, it usually assumes a monotonic relation between creditor protection and financial development. We present a theoretical model for a credit market with adverse selection in which an intermediate level of creditor protection is capable of implementing first best equilibria. This is in line with several other theoretical papers, both in general equilibrium and in partial equilibrium setups. From an empirical standpoint, we take advantage of legal reforms in some countries during the 1990's and 2000's to implement a strategy based on the treatment effects literature in order to investigate the impact in firm equity and debt of: (i) granting financially distressed firms the right to an automatic stay on assets during court-supervised reorganization; and (ii) allowing creditors to remove managers of firms in reorganization. We find that restricting automatic stay reduces all equity-related variables, and has no significant impact on debt. We find no significant impact of managerial removal on either debt or equity. Chapter two evaluates the empirical consequences of a bankruptcy reform on a poorly developed credit market. In early 2005, the Brazilian Congress approved a new bankruptcy law. The new legislation increased creditor protection and improved the efficiency of the bankruptcy system. Using data from Brazilian and non-Brazilian firms, we estimate, using two different treatment effects models, the effects of the bankruptcy reform on contractual and non-contractual debt variables. In general, both models yield similar results. Concerning contractual debt variables, we found a significant increase in both total debt and long-term debt, and a reduction in the cost of debt. We found no effect in the loans' ownership structure. Finally, in chapter three we develop an estimable equilibrium search model of credit that can be used to conduct ex-ante evaluation of institutional changes, such as bankruptcy laws. Economic literature has established a causal relationship between institutions (such as laws and regulations) and financial market development. While this qualitative conclusion is widely accepted in the literature, there is little evidence of its quantitative importance. With our framework, it is possible to estimate how debt contracts change in response to modifications in credit-related institutions. It is also possible to estimate how investments made by firms will be affected, as well as characterize the distribution of firm size, age, and productivity before and after the institutional change. In an empirical exercise, we use data from Brazilian firms to simulate the effects of changing creditors recovery rates on the total and the mean values of both capital and debt. We find that debt increases with lower recovery rates. In most cases, the same is true for the stock of capital.